The refined best-response correspondence in normal form games - Dieter Balkenborg; Josef Hofbauer; Christoph Kuzmics (Bielefeld University, Institute of Mathematical Economics (IMW), 2012)
This paper provides an in-depth study of the (most) refined best reply correspondence introduced by Balkenborg, Hofbauer, and Kuzmics (2012). An example demonstrates that this correspondence can be very different from the standard best reply correspondence. In two-player games, however, the refined best reply correspondence of a given game is the same as the best reply correspondence of a slightly modified game. The modified game is derived from the original game by reducing the payoff by a small amount for all pure strategies that are weakly inferior. Weakly inferior strategies, for two-player games, are pure strategies that are either weakly dominated or are equivalent to a proper mixture of other pure strategies. Fixed points of the refined best reply correspondence are not equivalent to any known Nash equilibrium refinement. A class of simple communication games demonstrates the usefulness and intuitive appeal of the refined best reply correspondence.
urn:nbn:de:0070-pub-26717370
Keywords: C62; C72; C73; 330; best-response correspondence; persistent equilibria; Nash equilibrium refnements; strict and weak dominance; strategic stability; Nichtkooperatives Spiel; Dynamisches Spiel; Gleichgewicht; Theorie